Exploring status of emergency drugs and vaccine development in Covid-19 pandemic: an update - Sharma, Alok (Virusdisease, 2021)
COVID-19 outburst initiated from the city of Wuhan in China in December 2019 and has been declared as a public health emergency of international concern. This pandemic portrays a spectrum of clinical complications, primarily affecting the respiratory system reported to be caused by a pathogen SARS-CoV-2 belonging to the family of beta coronavirus. Currently, the main objective of the government authorities of all affected countries and research organizations is to find a potential solution in the form of a pharmacological intervention or a vaccination to eradicate the disease and to have a long-term solution to deal with the pandemic. A multitude of anti-viral regimens is proposed based on the repurposing of currently available drugs for other issues or the compassionate use of drugs to immediately control and optimize the healthcare facilities. Meanwhile, a number of agencies are proposing new drug candidates to recreate the possibility of treating the disease. Similarly, a lot of research work is going on worldwide for the development of vaccination. Currently, a good number of candidates has finally reached the borders of Clinical Trials and are expected to be launched as soon as possible. However, the regulatory framework and authorization of these candidates is the most significant aspect of the whole scenario, which needs a specific set of time for validation purposes. The present work is widely focused on the general aspects of COVID-19 and the regulatory landscape for the emergency authorization of repurposed drug candidates, compassionate use of drugs, investigational entities, and vaccine development worldwide. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13337-021-00684-5.